2008
DOI: 10.3171/jns/2008/108/6/1088
|View full text |Cite
|
Sign up to set email alerts
|

Association of endovascular therapy of very small ruptured aneurysms with higher rates of procedure-related rupture

Abstract: Object Procedure-related rupture during endovascular therapy of intracranial aneurysms is associated with a mortality rate of more than one third. Previously ruptured aneurysms are a known risk factor for procedure-related rupture. The objective of this study was to evaluate whether very small, ruptured aneurysms are associated with more frequent intraprocedural ruptures. Methods This was a retrospective cohort study in which the investigators examined consecutive ruptured aneurysms treated with coil emboliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
145
3
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(160 citation statements)
references
References 13 publications
6
145
3
2
Order By: Relevance
“…Nguyen et al 3 reported a fivefold increase in the incidence of rupture during endovascular treatment of aneurysms that were Յ3 mm compared with larger aneurysms. To prevent this complication, careful microcatheter placement at the neck of the aneurysm and use of the soft coil loop to enter the aneurysm were useful.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nguyen et al 3 reported a fivefold increase in the incidence of rupture during endovascular treatment of aneurysms that were Յ3 mm compared with larger aneurysms. To prevent this complication, careful microcatheter placement at the neck of the aneurysm and use of the soft coil loop to enter the aneurysm were useful.…”
Section: Discussionmentioning
confidence: 99%
“…13 The small size of the aneurysm may be associated with a higher risk for rupture during embolization. 2,3 Review of the English-language literature revealed only 1 study by Suzuki et al, 4 who reported on endovascular treatment of very small aneurysms. However, they studied aneurysms of at least 3 mm with a favorable fundus-to-neck ratio of 1.5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have demonstrated an increased risk for perforation in small aneurysms. Nguyen et al 35 recently demonstrated that the risk for rupture increases from 2.3% for aneurysms more 36 We used abciximab (intravenously or intra-arterially) in 27 patients when thrombus was evident during the procedure, and there were no symptomatic thromboembolic events in 93% of these patients. One patient had an ischemic stroke in the motor cortex, and another had a subsequent hemorrhage from the treated aneurysm the following day and underwent craniotomy and clipping.…”
Section: Discussionmentioning
confidence: 99%
“…hemorrhagic complications of endovascular treatment of aneurysms occur more frequently with ruptured than unruptured aneurysms 2 , and more readily in small than large ruptured aneurysms 3 . The clinical consequences of these complications vary from one report to another 2,4,5 .…”
Section: Discussionmentioning
confidence: 99%